Визначення рівня уваги та індексу напруження водія в лабораторних умовах в різні періоди доби - Приходько, Всеволод; Черних, Володимира (Посвіт, 2019)
The level of attention of a person is studied with the help of a functional index. The research was carried out twice at different hours of the day, and also the statistical data of the analysis were established.
Determining the attention level by the functional indicator of the stress index in different periods of day
Keywords: 656.13